A review on solar chimney systems. (January 2017) - Kasaeian, A.B.; Molana, Sh.; Rahmani, K.; Wen, D.
Abstract: The increased utilization of solar energy has generated intensive interest in developing solar chimney (SC) technology in recent years. Many studies have been conducted in this area both experimentally and theoretically, whereas experimental studies are mainly focused on small-scale systems. This work provides a comprehensive and updated review that includes most of the experimental, analytical and simulational studies, the solar chimney applications, hybrid systems and geographical case studies based on extended references with different focuses in different sections. The technological gaps are identified and a summary of suggestions is given, including more experimental works on large-scale systems, and CFD analysis for optimization between geometrical parameters and output power. Further studies on some emerging applications of solar chimney technology including hybrid systems are also recommended.